The Implementation of Pancasila Education in Developing Discipline and Responsibility Character among Grade XI C Students at SMA Negeri 1 Sawan - Widyaningsih, Ni Wayan; Sanjaya, Dewa Bagus; Kertih, I Wayan; Wahyudi, Ni Putu Putri Audi Vebi; Listyani, Ni Putu Diana (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
Pancasila Education plays a strategic role in shaping students’ character, particularly discipline and responsibility. This study aims to describe the implementation of Pancasila Education in developing discipline and responsibility character among Grade XI C students at SMA Negeri 1 Sawan. This research employed a qualitative approach with a descriptive method. The research subjects included Pancasila Education teachers and Grade XI C students. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results showed that the implementation of Pancasila Education in strengthening discipline and responsibility character was carried out through classroom learning activities, habituation of disciplined behavior, responsibility-based assignments, and teacher role modeling. Furthermore, the integration of Pancasila values into learning activities and school programs contributed to the gradual development of students’ discipline and responsibility. Therefore, Pancasila Education plays an important role in building students’ character based on Pancasila values.